Book Review: Billetes. Del papel moneda a los billetes de banco en Costa Rica, by Manuel Chacón Hidalgo - Montero Mora, Andrea (2020)
A work about economic history is reviewed here, centered on the study of money and coin. It’s a work of scientific divulgation that analyses the process of coin consolidation in Costa Rica from the eighteenth century up to the year 2018. This periodization is chronologically ordered in six different eras, that match the six chapters in which the book is divided. In addition to this periodization of the history of coin, the text offers two hypotheses about the usage of coin; firstly, as a mechanism of social control, and secondly as an element of cultural change with the arrival of paper-money.